DAYA GUNA DIMENSI BAHASA DALAM UNDANG-UNDANG OTONOMI KHUSUS PAPUA - Warami, Hugo (Universitas Papua Manokwari, 2016)
This article aims to describe the use of language which is implemented through a legal document called a Special Autonomy Law on Papua in 2001 had a relative sense of status, socio-political situation and the condition of Papua in order to strengthen the frame of the Republic of Indonesia. This article is based on three assumptions that can be reviewed in further description of (1) the use of language in the political sphere Papua, (2) the relation distinctiveness political language in the statute of special autonomy to Papua, and (3) the ideology of political language has a relationship with the political situation Papua. Along with the construction of language as a tool used by humans to coordinate their actions in the context of social relationships. Then there is the use of a word in the language. If the language is seen as a tool, means the language is the act or acts and also instructions to do or perform the action.